The Effectiveness of Cooperative Learning Models Tai and Stad Type in Improving Student's Critical Thinking - Yhusita Tyas Margaretha; Agustina Tyas Asri Hardini (Eduvest - Journal of Universal Studies, 2021)
This study aims to determine the level of effectiveness of thecooperative learning model type TAI "Team AssistedIndividulization" and type STAD "Student Teams AchievementDivisions" as a learning model in improving the critical thinking ofelementary school students of class V in science subjects. Thisexperimental research was in the form of a Quasi ExperimentalDesign. The research design used is a quasi-experimental researchusing the nonequivalent control group design pattern. This researchis an experimental research conducted at SD Negeri Polobogo 03and SD Negeri Polobogo 02 which are located in Polobogo Village.The research was conducted from February to March in the secondsemester of the academic year 2021/2022 which was carried out inclass V. The samples in this study were obtained through probabilitysampling techniques with purposive random sampling type. Basedon the research results, the effectiveness of the cooperative learningmodel type TAI "Team Assisted Individulization" showed anaverage increase of 28.57% greater than the cooperative learningmodel type STAD "Student Teams Achievement Divisions" whichwas 26.75%. Based on the results of the research hypothesis testusing the mean difference test on the independent sample t-test, itshows that there is a significant difference between the cooperativelearning model of the TAI type "Team Assisted Individulization" andthe cooperative learning model of the STAD type "Student TeamsAchievement Divisions" in terms of ability results. critical thinkingof students in science subjects.